Ichnofauna from coastal meandering channel systems (Upper Cretaceous Tremp Formation, South-Central Pyrenees, Spain): delineating the fluvial-tidal transition. (1st July 2016) - Díez-Canseco, Davinia; Buatois, Luis A.; Mángano, M. Gabriela; Díaz-Molina, Margarita; Benito, M. Isabel
Abstract: The Upper Cretaceous "redbeds" of the lower Tremp Formation (South-Central Pyrenees, Spain) contains an ichnofauna consisting of Taenidium barretti, Taenidium bowni, Loloichnus isp., Arenicolites isp., Planolites isp., and Palaeophycus isp. This ichnofauna occurs in deposits formed in tide-influenced meander loops and their associated overbank mudflats. Evaluation of the taphonomic controls on the Tremp ichnofauna shows that (1) two morphotypes of Taenidium barretti are controlled by the substrate consistence, (2) Arenicolites may be enlarged by erosion processes, and (3) Taenidium barretti and Planolites isp. are not the same ichnotaxa showing different types of preservation. The meniscate fill in Taenidium barretti suggests that this structure was produced by deposit feeders. The Tremp ichnofauna is grouped into two trace-fossil assemblages, a depauperate subaquatic monospecific Planolites suite and an assemblage representing the Scoyenia Ichnofacies. Trace-fossil distribution reflects paleoenvironmental changes in the meandering channels along the stratigraphic section with the Planolites suite in the lowermost part of the lower interval and the Scoyenia Ichnofacies in the middle and upper intervals. The lowermost suite may be likely formed seaward of the maximum salinity limit, under extreme brackish-water conditions, whereas the Scoyenia Ichnofacies records a freshwater assemblage that was formed landward of the maximum salinity limit, reflecting deltaic progradation.